(untitled) (Research, Society and Development, 2020)
Objective: to characterize the Brazilian production of theses and dissertations on the culture of patient safety in a hospital environment, identifying the trends of this production. Method: narrative review study, carried out in the catalogue of theses and dissertations of the Catalogue of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, carried out in January 2020. Results: 23 studies were reviewed. The trend was identified as dissertation studies, produced by nursing in the Southeast region, under the quantitative approach, using validated questionnaires and published 2017. The hospital environment is the main scenario of study, followed by intensive care units, which approached the nursing team. There was a predominance of negative or fragile safety culture. It is noteworthy that the improvement of safe health care practices can help in the consolidation and resolution of the actions proposed by health services. Final considerations: there are needs and possibilities for changes in the quality of services, given the opportunity for a favorable environment. Therefore, there is the need to strengthen the Patient Safety Centers of health institutions, especially hospital ones, which requires institutional investment in risk management and dissemination of permanent education actions to strengthen safe practices.